The Reasons Why Jurists and Scholars Abandon Relying on Authentic Hadiths in Legal Argumen-tation. - Muhammad, Faraj Al Mabrouk Adam (Al-Mukhtar Journal of Social Sciences, 2024)
The Sunnah holds the second position in legal rulings after the Quran when invoked in religious matters. It is the second source of legislation, viewed both as obligatory to follow and as divine revelation similar to the Quran. However, it is considered secondary in terms of legal authority because the Quran is comprehensive and detailed, while the Sunnah supplements it without the same level of detail. Scholars have established a scientific methodology for dealing with Prophetic Hadiths regarding their authenticity and implications, setting conditions for accepting the text and deriving rulings from it. Due to some people's lack of understanding on how to invoke the Sunnah and preoccupation with contentious subsidiary issues, there are those who consider all authentic Hadiths as indisputable evidence in any jurisprudential matter without considering abrogation, abrogated, preponderance, and balance, despite their authenticity. To address this confusion, this research is presented with the title: "Reasons why Jurists and Scholars Abandon Relying on Authentic Hadiths in Legal Argumentation
Keywords: Sunnah; Scholars; Prophetic hadith